(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Health care leaders and frontline workers have experienced significant mental health challenges during the COVID-19 pandemic. Building on insights from the 2002–2003 SARS outbreak, which saw early signs of acute stress disorder in quarantined health care workers, it is clear that pandemics place an extraordinary psychological burden on these frontline health care workers. Common symptoms among health care leaders include fatigue, social withdrawal, fear of patient contact, anxiety, insomnia, impaired decision-making, and a reduced desire to continue working in health care settings. Long-term consequences such as PTSD, depression, and substance abuse have also been documented. Recent research during the COVID-19 pandemic further confirms these trends, with anxiety (36%), depression (20%), and sleep disorders (24%) among health care workers. These findings underscore the pressing need for ongoing mental health support and institutional resilience strategies for healthcare leaders during and after the pandemic.